Firm-level and technology transfer in Chinese engineering, procurement and construction projects in the Philippines - Diokno, Harold A.
In recent years, the Philippine has experienced a relative increase in Chinese economic projects. Most of the infrastructure projects have been done though engineering, procurement, and construction (EPC) projects or turnkey agreements with Filipino firms. The goal of this study is to identify and examine the extent and presence of knowledge and technology transfer (KTT) that happens in the joint ventures. In addition, the study also explores the absorptive capacity of local firms, in hopes that such transfers would benefit and increase the capabilities of the local industry in the long run. For the purpose, interviews were conducted to gather firm-level data among decision-makers and project managers in EPC firms. The data gathered were analyzed according to the frameworks on KTT types, modes of transfer, and absorptive capacity. The results establish the extent and potential of KTT in the country and reveal a number of opportunities that local firms could harness to their advantage in terms of such crucial learning from Chinese firms. The study further recommends that an industry or country level analysis be pursued to provide a larger picture of how KTT could contribute to the economic development of the country.